1997
DOI: 10.1097/00005392-199707000-00052
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Patients With Metastatic (Stage D2) Prostate Cancer: Experience from the Scandinavian Prostatic Cancer Group Study-2

Abstract: These data indicate that computerized nuclear texture analysis as well as up regulation of sialyl Lewis(x) molecules may be new important prognostic factors in metastatic prostate cancer. Furthermore the prognostic importance of sedimentation rate, alkaline phosphatase and hemoglobin was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
27
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
5
27
1
4
Order By: Relevance
“…9,12 In the current study, the median overall survival of patients with Gleason scores .8 was significantly shorter than that of the lower scoring patients, which is consistent with our previous study. 6 Cheville et al 13 and Yigitbasi et al 9 have also reported that among patients with bone metastases, the Gleason score of the primary prostate adenocarcinoma is strongly associated with patient outcome.…”
Section: Discussionsupporting
confidence: 92%
“…9,12 In the current study, the median overall survival of patients with Gleason scores .8 was significantly shorter than that of the lower scoring patients, which is consistent with our previous study. 6 Cheville et al 13 and Yigitbasi et al 9 have also reported that among patients with bone metastases, the Gleason score of the primary prostate adenocarcinoma is strongly associated with patient outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Serum ALP level has been found to be an important prognostic factor in many studies. [15][16][17] Our results agree with the data from the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Other reports suggested prognostic value of serum T level as well as performance status, serum alkaline phosphatase level, the extent of disease grade on bone scan in stage D2 patients [2][3][4][5][6][7][8][9][10]. Until now, however, no testosterone data was available for Japanese men with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A NUMBER of clinical, endocrinological and pathological prognostic factors for prostate cancer have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Knowledge of these factors will likely contribute to determining the most appropriate therapy for individual patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation